Challenges in the Laboratory Diagnosis of Thrombophilia: An In-Depth Review of Current Issues and Approaches - Nuli, Basmah Abdullah; Alrefaei , Raweyah Mohammad; Masmali , Abdulrahman Yahya Hadi; Bahkali, Amgad Ali Mohd; Alharbi , Turki Awad Ageel; Gamilah , Mohammed Ali Ibrahim Abu; Almadani, Laila Basheer Mohd (Journal of Ecohumanism, 2024)
Background: Venous thromboembolic disease (VTD) is influenced by various biological, medical, and ecological risk factors, with thrombophilia representing an acquired or hereditary predisposition to venous thromboembolism (VTE). The complexity of identifying suitable candidates for thrombophilia testing and interpreting results greatly complicates clinical management. Methods: This review evaluates traditional inherited thrombophilia, including deficiencies in natural anticoagulants and mutations such as factor V Leiden and prothrombin G20210A. It emphasizes the necessity of molecular diagnostics over traditional plasma tests, particularly in patients undergoing direct oral anticoagulant (DOAC) therapy. The review also discusses the timing of thrombophilia testing and the role of genotyping. Results: The findings reveal that the presence of DOACs can significantly interfere with laboratory assays for thrombophilia. Functional assays for antithrombin, protein C, and protein S demonstrate variability in sensitivity to DOACs, leading to potential false-negative results. The review highlights the importance of neutralizing DOACs before testing to ensure accurate results and explores emerging adsorbent methods to eliminate DOAC interference. Conclusion: The laboratory diagnosis of hereditary thrombophilia is increasingly challenging due to the widespread use of DOACs. Enhanced understanding of how these medications affect testing is crucial for accurate diagnosis and treatment. The review suggests that specialized laboratories should conduct thrombophilia assessments in patients on DOACs to improve diagnostic accuracy and clinical outcomes